2018
DOI: 10.1038/s41588-018-0191-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective gene dependencies in MYCN-amplified neuroblastoma include the core transcriptional regulatory circuitry

Abstract: Childhood high-risk neuroblastomas with MYCN gene amplification are difficult to treat effectively. This has focused attention on tumor-specific gene dependencies that underlie tumorigenesis and thus provide valuable targets for the development of novel therapeutics. Using unbiased genome-scale CRISPR-Cas9 approaches to detect genes involved in tumor cell growth and survival, we identified 147 candidate gene dependencies selective for MYCN-amplified neuroblastoma cell lines, compared to over 300 other human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
337
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 230 publications
(357 citation statements)
references
References 44 publications
20
337
0
Order By: Relevance
“…We therefore profiled genome-wide distribution of H3K27Ac by ChIP-sequencing of JQ1 naive and resistant cells across both cell line models (Fig S3I-P). In concordance with previous studies, SE-associated genes: HAND1/2, GATA3, and PHOX2B , were identified in naive cells (Boeva et al, 2017; Chipumuro et al, 2014; van Groningen et al, 2017, Durbin et al, 2018). SE-marked genes and typical enhancer (TE)-marked genes, defined by high H3K27Ac signal in enhancer regions, were preferentially repressed by JQ1 (Figure S4A, B).…”
Section: Resultssupporting
confidence: 91%
“…We therefore profiled genome-wide distribution of H3K27Ac by ChIP-sequencing of JQ1 naive and resistant cells across both cell line models (Fig S3I-P). In concordance with previous studies, SE-associated genes: HAND1/2, GATA3, and PHOX2B , were identified in naive cells (Boeva et al, 2017; Chipumuro et al, 2014; van Groningen et al, 2017, Durbin et al, 2018). SE-marked genes and typical enhancer (TE)-marked genes, defined by high H3K27Ac signal in enhancer regions, were preferentially repressed by JQ1 (Figure S4A, B).…”
Section: Resultssupporting
confidence: 91%
“…Accumulating evidence indicates that tumor cells are driven by a small set of transcription factors (TFs) that control global gene expression programs (Durbin et al, 2018;Mansour et al, 2014;Sanda et al, 2012). While disused in corresponding healthy cells, some tumor-driving master transcription factors (MTFs) are often developmental regulators that are aberrantly expressed and functionally co-opted to regulate tumor cell states.…”
Section: Introductionmentioning
confidence: 99%
“…For example, regulators of T cell development, TAL1, GATA3, RUNX1, and MYB, are over-expressed and coregulate oncogenic programs in T-cell acute lymphoblastic leukemias (Mansour et al, 2014;Sanda et al, 2012). Additionally, developmental regulators MYCN, HAND2, ISL1, PHOX2B, GATA3, and TBX2 have been identified as MTFs in neuroblastoma (Durbin et al, 2018). MTFs are generally expressed in only a limited number of cell types, consistent with their potent role in establishing a gene expression program that drives cell identity (D'Alessio et al, 2015;Whyte et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations